Measuring Fiscal Vulnerability and Fiscal Stress : A Proposed Set of Indicators - McHugh, James (IMF Working Papers; Working Paper ;, 2011)
This paper proposes a set of fiscal indicators to assess rollover risks using the conceptual framework developed by Cottarelli (2011). These indicators provide early warning signals about the manifestation of these risks, giving policymakers the opportunity to adjust policies before extreme fiscal stress events. Two aggregate indices are calculated: an index of fiscal vulnerability and an index of fiscal stress. Results show that both indices are elevated for advanced economies, reflecting unfavorable medium-term debt dynamics and aging-related spending pressures. In emerging economies, solvency risks are lower, but the composition of public debt remains a source of risk and the fiscal position is weaker than before the crisis.